Creating a Culture of Outreach and Partnerships - Jeffrey Ward (Academic Chairpersons Conference Proceedings, 2023)
The presenter will share his experience building a culture of outreach and partnership development between the university and external stakeholders. Describing his college’s Council of Outreach and Arts Entrepreneurship, the presenter will share partnership building best practices that are generalizable to various departments regardless of discipline, size, scope, or mission.
Keywords: Partnerships; Interdisciplinary; Faculty Engagement; Outreach